The APPGM-SDG Solution Projects: Empowering Women Through Mobilising Grassroot Communities - Azmi, Zaireeni; Selamat, Nor Hafizah; Endut, Noraida (Journal of Technical Education and Training, 2025)
In 2019, the Malaysian Parliament established the All-Party Parliamentary Group Malaysia on the Sustainable Development Goals (APPGM-SDG) to offer multi-party collaborations related to the sustainable development goals (SDG). This article evaluates its key programme, the Solution Providers Projects. The article’s primary objective is to showcase the work and activities of grassroots communities in promoting gender equality and women’s empowerment, goal 5 of the SDG. It analyses projects led by women, those exclusively benefiting women, and those substantially involving women's participation. The paper also aims to assess how these projects' outcomes contribute to gender equality and women’s empowerment and assists women to pursue TVET opportunities and skills. In the Northern Region which covers several districts in Penang and Perak, 22 projects were evaluated of which nine specifically address women's needs. The study employed a qualitative approach to data collection including observations, focus group discussions (FGDs), and document analysis from November 2023 to February 2024. The participants for FGD were selected among the beneficiaries of the 22 projects. The elements of empowerment-resource, agency, and achievements were evaluated by analysing six domains of APPGM-SDG model: Deep, Wide, Clear, High, SDG, and Gender. The main findings indicate that these projects with TVET opportunities and skills development foster greater economic and social inclusion while empowering women, creating opportunities that uplift them, benefit the broader community and promoting gender equality. Additionally, some projects have ensured diversity and inclusion among their targeted beneficiaries, thus achieving multiple SDGs within a single project. This comprehensive evaluation underscores the critical role of grassroots communities in advancing sustainable development and community well-being.